THE IMPORTANCE OF K. STANISLAVSKY'S SYSTEM IN CREATING A CHARACTER (IMAGE) BY A THEATER ACTOR - Egamberdiyev Jasurbek Eshqobilovich (Bright Mind Publishing, 2025)
This article analyzes the importance of K.S. Stanislavsky's system widely used in theatrical art for character creation by actors, its basic principles, and its role in modern theater. The article examines the stages, methodology, and practical significance of Stanislavsky's system in the process of character creation.
Keywords: K.S. Stanislavsky, character creation